O (re)dimensionamento da temporalidade laboral na vivência de professores tutores da educação on-line - Ponte, Felipe Teófilo (2015)
This study was conducted between 2013 and 2015, with the search field the scope of the Distance Learning online and type as the subjects participating Letters Course tutors (Portuguese-English-Spanish) of an institution of public higher education. The objective of this study was to investigate how online education teachers experience resizing the labor temporality. Through qualitative approach, focusing on speeches by professionals in question, spoke about the relationship between the categories of time and effort in order to critically analyze the changes in the working structure and the repercussions that these changes produced in the constitutions subjective workers. By applying semi-structured interviews and methodological resource of hermeneutics social discourse analysis, analyzed how these professionals build and reproduce the temporal system in their work activities. The speeches of the participants highlighted a labor configuration demarcated by a temporal variability and the absence of a time of rigid and inflexible work. In addition, there was a work temporality that is diluted to other social times past, in most cases, to interfere in the daily lives of these professionals. Signs of insecurity emerged in the speeches of tutors such as: accumulation of tasks, fast-paced and intense speed of work, demand for versatility, versatility and flexibility, work devaluation, not professionalization, stretching labor hours. As a result of this study, it was found, then the professor of online education a social agent that explicit in your reality the imperatives of the flexible mechanisms of production.